Estrogen-alone therapy and invasive breast cancer incidence by dose, formulation, and route of delivery: findings from the WHI observational study. Issue 9 (September 2018) - Shufelt, Chrisandra; Bairey Merz, C. Noel; Pettinger, Mary B.; Choi, Lydia; Chlebowski, Rowan; Crandall, Carolyn J.; Liu, Simin; Lane, Dorothy; Prentice, Ross; Manson, JoAnn E.
Abstract: Objective: Research on the relationships between different hormone therapy doses, formulation and routes of delivery, and subsequent breast cancer incidence has been limited. This study directly compared different estrogen doses, formulations, and route of delivery of estrogen alone among women with a hysterectomy in relation to invasive breast cancer incidence. Methods: The Women's Health Initiative Observational Study is a large multicenter prospective cohort study conducted at 40 US sites. Analyses included 26, 525 postmenopausal women with a hysterectomy, aged 50 to 79 years, at study entry, recruited between September, 1993 and December, 1998, with annual follow-up through September 12, 2005. Results: Average follow-up was 8.2 years. For conjugated equine estrogen (CEE) users, no difference was observed between low-dose CEE (<0.625 mg) compared with conventional-dose CEE (0.625 mg) for breast cancer (hazard ratio [HR] 0.99, 95% confidence interval [CI] 0.65, 1.48)]. Compared with conventional-dose CEE, transdermal estrogen was associated with a nonsignificant lower risk of invasive breast cancer (HR 0.75, 95% CI 0.47, 1.19). The low prevalence of transdermal use likely limited power for this comparison, and for a comparison of oral estradiol to conventional-dose CEE (HR 1.20, 95% CI 0.84, 1.39). Conclusion: Our results indicate that invasive breast cancer risk did not differ appreciably in women with a hysterectomy using estrogen-alone when directly comparing different doses, formulations, and routes of delivery to the conventional oral CEE. These findings suggest that the lower breast cancer risk found in the WHI estrogen-alone trial may extend to lower doses of CEE. Additional research is needed to confirm these hypotheses. Abstract : Supplemental Digital Content is available in the text